Perancangan Sistem Recloser Untuk Memantau Konsumsi Daya Listrik Rumah Tangga Menggunakan Modifikasi Arduino Mega - Ath-Thaariq, Bhakti; Liswanto, Budi; Diki, Moh (CV. Sekawan Siji, 2025)
This paper discusses the design of a recloser system to monitor electricity consumption using a modified Arduino Mega. Excessive use of electrical devices, cables that are too small to handle the current load, or disturbances in the electrical system. As a result, cables or electrical devices can overheat and cause fires or even damage to electrical equipment. To address these problems, the reliability and safety of household electrical installations use a protection system. Protection equipment on a household scale is called (MCB) Miniature Circuit Breaker. The design uses a PZEM-004T sensor, Arduino Mega 2560, relay, and Recloser prototype. The system is designed to detect overload disturbances above the 2 Ampere MCB limit or short circuits in real time and displays power 12.38, 384.8, 376.4 watts, voltage 230.7, 228.2, 228.1V, and current 0,06, 1,29, 1,26A monitoring in the recloser modification system on household-scale electricity consumption. The recloser modification system will work or try to turn ON again when the problem is detected for 3 attempts to enter and will return to normal automatically when the recloser modification system detects that the overload has been resolved by reducing the load or when a short circuit occurs when the Recloser tries to re-enter between 1 and 3 attempts, if it exceeds 3 attempts then the system is permanently OFF and must be reset manually.